Atlantic Wall and Other Poems - Colie, Rosalie L. (Book collections on Project MUSE., 1974)
A noted historian of Renaissance English literature and scholar of comparative literature, Rosalie L. Colie was also a serious poet. This volume brings together 31 of her poems, illustrating the striking interplay between her scholarship and her personal response to the world. The title poem and the shorter poems that follow testify to Professor Colie's versatility as a poet. There are sonnets, elegies, metaphysical speculations, pastorals, love poems all imbued with the intelligence and sensibility that pervaded her life and work. Originally published in 1975. The Princeton Legacy Library.